Spectral Enhancement of Organic Photodetectors - Rauch, Tobias (KIT Scientific Publishing, 2014)
Solution-processed photodiodes with infrared sensitivities at wavelengths beyond the bandgap of silicon would be a significant advance towards cost-effective imaging. Colloidal quantum dots are highly suitable as infrared absorbers for photodetection. The concept of organic bulk heterojunctions sensitized with PbS nanocrystalline was proved with efficient near-infrared detection up to 1.8 mm for NIR imaging on active matrix TFT backplanes and demonstrated x-ray sensitivity.